2015
DOI: 10.1080/00933104.2014.1001106
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Think Politically: Toward More Complete Disciplinary Knowledge in Civics and Government Courses

Abstract: Secondary civics and government courses are often framed as a content area in which students learn about processes of government and ways of participating in a democratic society, as opposed to a discipline in which students use specific tools and ways of thinking that mimic those used by professionals within that discipline. In this article, we call for an increased emphasis on disciplinary knowledge in civics and government courses, specifically knowledge that utilizes the tools and methodologies of politica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Hoskins et al, 2012;Sohl & Arensmeier, 2015), we should strengthen further the bottom-up perspective on politics, focusing on the (extended) public sphere as a central arena for participation. This focus includes empowering students through participation in discussions, practice in facing opposition and critically reviewing arguments and political information in social media (Journell et al, 2015), including rhetoric with emotional appeal. A strong focus on the bottom-up perspective of politics does not reduce the importance of knowledge about political institutions and formal politics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoskins et al, 2012;Sohl & Arensmeier, 2015), we should strengthen further the bottom-up perspective on politics, focusing on the (extended) public sphere as a central arena for participation. This focus includes empowering students through participation in discussions, practice in facing opposition and critically reviewing arguments and political information in social media (Journell et al, 2015), including rhetoric with emotional appeal. A strong focus on the bottom-up perspective of politics does not reduce the importance of knowledge about political institutions and formal politics.…”
Section: Discussionmentioning
confidence: 99%
“…A strong focus on the bottom-up perspective of politics does not reduce the importance of knowledge about political institutions and formal politics. However, we should ask what is important knowledge about politics, so teachers and students can focus on in-depth understanding of political processes and the tools and methods of social-scientific enquiry to critically evaluate political information (Journell et al, 2015). Such a bottom-up, empowermentfocused perspective may be considered na€ ıve.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have analyzed how educators can skillfully guide students to examine multiple sides of controversial issues (e.g., Hess & McAvoy 2015), but there has been limited research on how educators teach about presidential elections. Some valuable studies have explored pedagogies for exploring candidates' backgrounds (Journell 2011a) and positions (Journell 2011b), and others have documented students' civic development through election simulations (Coffey, Miller & Feuerstein 2011;Day, Boeckelman, LaFrance, Hardy & Rohall 2012) and disciplinary literacy strategies (Journell, Beeson, & Ayers 2015). And our own recent study found that watching and then discussing presidential debates can strengthen students' political interest (Levy, Solomon, & Collet-Gildard, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…In YPAR students use the tools of social science to investigate issues in their communities that they themselves identified, and they use their research findings to work for community change (e.g., Cammarota and Romero, 2009;Hubbard, 2015;Irizarry, 2009). YPAR is one way of bringing to life Journell, Walker Beeson, and Ayers's (2015) finding that high-quality civics education equips students to be critical consumers of political knowledge and that this is done through the teaching and application of the disciplinary tools of the social sciences. Osler (2015) similarly argues that combining official curricula with learners' own experiences, identities, and values is essential for the cultivation of active citizens.…”
Section: Reviewing the Literature On Civics And Bilingual Educationmentioning
confidence: 99%